The Relationship between Accounting Information Disclosure and Decision-Making among Investors in China - Feng, Ziyang; Kishan, K. (Journal of Ecohumanism, 2024)
Financial scandals and worldwide corporate failures have been attributed to persistent information asymmetry to discerning investors. The study focuses on the relationship between accounting information disclosure and decision-making among investors in China. The analysis of research papers is based on searching for keywords related to decision-making in various published journals, conference proceedings, working papers, and other published books. These documents were collected over a period of one year, from the publication of the most informative paper providing a fundamental foundation for the field (2016) to the latest paper (2024). These articles are classified by bias, year, country, and author. All research tools related to primary and secondary data used by the author are also included in our findings. A new era of understanding human emotions, behaviors, and moods has begun, which was previously dominated by financial market research. In addition, this field has not only attracted the attention of scholars, but also various enterprises, financial intermediaries, and entrepreneurs, thus its importance has been enhanced. This review focuses on individual and institutional investors as well as financial advisors, but attention should be paid to the behavior of some investors who invest through intermediaries, narrowing the population down to various variables and targeting the expanding economy to obtain some unexplainable theories. The study therefore favours the full disclosure of all accounting information to assist the investors in making wise decision on their investments in China, as this is the only way by which corporate failures could be reduced to the barest minimum if not completely eliminated. It is therefore recommended that financial statement preparers should ensure full disclosure practices to support meaningful investment decisions in order to improve the market value of the company.